Complications and donor site morbidity of 3‐layer reconstruction with iliotibial tract of the anterior skull base: Retrospective analysis of 186 patients. Issue 1 (30th October 2017) - Mattavelli, Davide; Schreiber, Alberto; Villaret, Andrea Bolzoni; Accorona, Remo; Turri‐Zanoni, Mario; Lambertoni, Alessia; Ferrari, Marco; Castelnuovo, Paolo; Nicolai, Piero
Abstract: Background: Anterior skull base reconstruction after resection of sinonasal cancers may be challenging when pedicled flaps are unavailable. The purpose of the present study was to analyze the complication rate and donor site morbidity of 3‐layer reconstruction with the iliotibial tract (ITT). Methods: We retrospectively reviewed all anterior skull base reconstructions with ITT performed from 2007 to 2015. Donor site morbidity was investigated by a dedicated questionnaire. Factors impacting on cerebrospinal fluid (CSF) leak were assessed using the Fisher's exact test. Results: One hundred eighty‐six patients were included. The overall complication rate was 9.7%. A CSF leak occurred in 11 patients (5.8%). Twenty patients (10.8%) and 130 patients (69.9%) underwent previous or adjuvant radiotherapy, respectively. Neither radio(chemo)therapy nor age impacted the risk of CSF leak. Six patients (3.2%) experienced complications at the donor site. The questionnaire demonstrated minimal functional and aesthetic morbidity. Conclusion: Three‐layer reconstruction with the ITT is a safe procedure with acceptable complication rate and donor site morbidity.